2021
DOI: 10.1186/s12284-021-00489-6
|View full text |Cite
|
Sign up to set email alerts
|

Plastid caseinolytic protease OsClpR1 regulates chloroplast development and chloroplast RNA editing in rice

Abstract: Background Plant plastidic caseinolytic protease (Clp) is a central part of the plastid protease network and consists of multiple subunits. The molecular functions of many Clps in plants, especially in crops, are not well known. Results In this study, we identified an albino lethal mutant al3 in rice, which produces albino leaves and dies at the seedling stage. Molecular cloning revealed that AL3 encodes a plastid caseinolytic protease, OsClpR1, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In tomatoes, ClpR1 regulates both the accumulation of carotenoids and the ripening of tomato fruit [23]. In rice, the mutation of OsClpR1 results in albino leaves and plant death at the seedling stage and affects the transcript levels of chlorophyll biosynthesis and chloroplast development-related genes [42]. OsClpP6 has been reported to affect the development of rice chloroplasts [24], the growth of leaves, and the mutation of OsClpP6 in rice (nal9), resulting in a phenotype of narrow leaves [25].…”
Section: Discussionmentioning
confidence: 99%
“…In tomatoes, ClpR1 regulates both the accumulation of carotenoids and the ripening of tomato fruit [23]. In rice, the mutation of OsClpR1 results in albino leaves and plant death at the seedling stage and affects the transcript levels of chlorophyll biosynthesis and chloroplast development-related genes [42]. OsClpP6 has been reported to affect the development of rice chloroplasts [24], the growth of leaves, and the mutation of OsClpP6 in rice (nal9), resulting in a phenotype of narrow leaves [25].…”
Section: Discussionmentioning
confidence: 99%
“…6). Previous studies found that some rice albino mutants exhibit chloroplast RNA editing defects (Liu et al 2021;Wang et al 2021b). However, some studies indicate that the defective RNA editing cannot cause the albino phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide dismutase gene ALM1 can also interact with PEP complex OsTRXz and regulate chloroplast development by affecting the content and activity of reactive oxygen species in rice [62][63][64]. Mutation of the AL3 gene, which encodes a plastid caseinolytic protease, causes albino leaves and seedling death in rice [34].…”
Section: Introductionmentioning
confidence: 99%